Comparative study on the drying mechanisms and characteristic changes of fabrics according to heat transfer principles - Jiyul Lee; Jaeyong Cho; Suhyun Lee (Fashion and Textiles)
Abstract Microwave-convection (MWC) drying was compared with hot air-convection (HAC) drying to elucidate the differences in the drying characteristics of fabrics based on the moisture type and drying performance. For a single fabric, free water removal was more effective with MWC drying, whereas HAC drying was better suited for bound water removal. For stacked fabrics, the moisture leveling effect of MWC drying enabled a uniform drying of the fabric, evaporating both free water and bound water. The dimensional change of MWC was lower than that of HAC, and the toughness and fiber morphology of the fabrics dried using MWC were comparable to those of untreated fabrics. Furthermore, MWC drying exhibited a higher energy efficiency with increasing fabric loads. The lower drying performance of HAC drying was attributed to the convection of hot air and the limitation of heat conduction. The findings of this study are expected to help develop automatic drying algorithms for household dryers.